2017
DOI: 10.3389/fpsyt.2017.00257
|View full text |Cite
|
Sign up to set email alerts
|

Neuroligin 2 R215H Mutant Mice Manifest Anxiety, Increased Prepulse Inhibition, and Impaired Spatial Learning and Memory

Abstract: Neuroligin 2 (NLGN2) is a postsynaptic adhesion protein that plays an essential role in synaptogenesis and function of inhibitory neuron. We previously identified a missense mutation R215H of the NLGN2 in a patient with schizophrenia. This missense mutation was shown to be pathogenic in several cell-based assays. The objective of this study was to better understand the behavioral consequences of this mutation in vivo. We generated a line of transgenic mice carrying this mutation using a recombinant-based metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
(41 reference statements)
3
29
0
Order By: Relevance
“…The low expression level of NL2 in our R215H KI mice distinguishes our KI mice from the NL2 KO mice, which showed completely absent expression of NL2 in our Western blot analysis. Furthermore, our R215H KI mice also showed clear GABAergic deficits as expected, but it is unknown whether their KI mice have any GABAergic deficits or not [ 8 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The low expression level of NL2 in our R215H KI mice distinguishes our KI mice from the NL2 KO mice, which showed completely absent expression of NL2 in our Western blot analysis. Furthermore, our R215H KI mice also showed clear GABAergic deficits as expected, but it is unknown whether their KI mice have any GABAergic deficits or not [ 8 ].…”
Section: Discussionmentioning
confidence: 84%
“…Surprisingly, our former collaborator Dr. Chia-Hsiang Chen’s group recently reported that their NL2 R215H KI mice displayed an increased pre-pulse inhibition phenotype [ 8 ]. However, because the startle response of their KI mice was not reported, it makes the data difficult to compare with ours.…”
Section: Discussionmentioning
confidence: 99%
“…A nonsense variant in Nlgn2 was recently identified in a patient with severe anxiety and autism 72 , in addition to Nlgn2 mutations previously associated with schizophrenia 2 . In mice, both the deletion of Nlgn2 and a schizophrenia-associated Nlgn2 mutation, R215H, result in severe anxiety phenotypes 74 , 75 , 111 . Nlgn2 is expressed both in the BLA and (to a lesser extent) CeA of mice 74 , but interestingly appears to play very different roles in these two structures.…”
Section: Molecular Determinants Of Anxiety In the Amygdalamentioning
confidence: 99%
“…It is generally accepted that the standard duration of the EPM is 5 min. However, based on the previous results by Chen et al ( 2017 ) and our group, we eventually decided to perform the EPM for 6 min, which should be validated in the future (Xing et al, 2013 ; Chen et al, 2017 ). Moreover, although we selected the performing time of the behavioral experiments based on published articles and our preliminary experiment, this decision may have rendered the behavioral results of the CD group incomparable with those of other similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the EPM test as previously described (Pellow et al, 1985 ; Liu et al, 2014 ; Chen et al, 2017 ). Briefly, the apparatus was composed of two open arms (25 × 5 cm) and two closed arms (25 × 5 × 20 cm).…”
Section: Methodsmentioning
confidence: 99%